Stephen Seiler on how the best train - Seiler, S. (Supporting champions, 2020)
I would put this week`s guest into a very select place in the world of endurance, one that has combined four often distinct factors, first quality academic research, second in a topic that contributes to elite performance, third creates a paradigm shift that challenges how most of us think about training, and fourthly has been successfully applied to the non-elites, the serious amateur athletes or training for the general population.